2005
DOI: 10.1086/430933
|View full text |Cite
|
Sign up to set email alerts
|

High Level ofvar2csaTranscription byPlasmodium falciparumIsolated from the Placenta

Abstract: Plasmodium falciparum parasites that bind to chondroitin sulphate A (CSA) express unique variant surface antigens that are involved in the placental sequestration that precipitates pregnancy-associated malaria (PAM). Two var gene subfamilies, var1csa and var2csa, have been associated with CSA binding. We show here that placental P. falciparum isolates highly transcribed var2csa but not var1csa. var2csa was not transcribed or was only minimally transcribed by parasites isolated from nonpregnant women. Placental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(101 citation statements)
references
References 15 publications
3
96
1
1
Order By: Relevance
“…In both cases, adhesion was attributed to the DBL␥ domain of PfEMP1. However, subsequent studies have not corroborated these findings and suggest that transcription of at least FCR3.varCSA is not associated with adhesion to CSA (9,10,25,35,40,41). A more promising candidate CSA binding parasite ligand is the VAR2CSA PfEMP1 identified by Salanti et al (36).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In both cases, adhesion was attributed to the DBL␥ domain of PfEMP1. However, subsequent studies have not corroborated these findings and suggest that transcription of at least FCR3.varCSA is not associated with adhesion to CSA (9,10,25,35,40,41). A more promising candidate CSA binding parasite ligand is the VAR2CSA PfEMP1 identified by Salanti et al (36).…”
mentioning
confidence: 98%
“…These studies also did not detect var2csa because it lacks the DBL␣ and DBL␥ domains for which the degenerate primers were designed. Quantitative analyses of var transcription in placental isolates have been restricted to comparisons of var2csa and FCR3.varCSA (35,40). These studies were suggestive of a major role for var2csa in malaria during pregnancy and excluded a similar role for FCR3.varCSA but did not address the potential roles of other var genes possessing DBL␥ domains that may also have been transcribed at high levels in placental isolates.…”
mentioning
confidence: 99%
“…A unique subset of VSAs that binds to chondroitin sulfate A has been identified on placental isolates of P. falciparum. The best-characterized variant is VAR2CSA, which is sex specific and highly transcribed [39,40]. Also, as we have seen, the variant proteins from parasites that cause severe malaria in non-immune patients differ from those expressed by parasites that cause uncomplicated malaria [32,41].…”
Section: Asexual-blood-stage Vaccinesmentioning
confidence: 88%
“…A further challenge with VAR2CSA (the dominant PAM antigen identified) like with other blood-stage antigens including MSP1 and AMA1 (Stowers et al, 2002) relates to sequence polymorphism and the question of how many variants would need to be included in a vaccine for optimal efficacy. Although var2csa is structurally conserved between P. falciparum isolates and is consistently over-expresssed by placental isolates (Duffy et al, 2006;Tuikue Ndam et al, 2005), multiple var2csa alleles were found in field isolates (Dahlback et al, 2006).…”
Section: Challenges To Developing a Malaria Vaccinementioning
confidence: 95%
“…Efforts to identify VSAPAM have largely focused on PfEMP1, a variant antigen implicated in several adhesive interactions (reviewed in Miller et al, 2002). VAR2CSA, the PfEMP1 protein encoded by the var2csa gene, has then been identified as the VSA involved in PAM (Salanti et al, 2003;Tuikue Ndam et al, 2005;Duffy et al, 2005;Duffy et al, 2006). This protein is constituted of six Duffy binding like (DBL) domains, at least four of them possessing the ability to bind CSA.…”
Section: Identification Of the Main Vsa Pam Var2csa-pfemp1mentioning
confidence: 99%